Recent advancement in daignosis of gastrointestinal diseases - Saraswat, Pranit; Khare, Pragati; Tiwari, Ritesh (Creative Pharma Assent, 2015)
Gastrointestinal diseases refer to ulcerative disorders of the upper gastrointestinal tract. Stomach acids and some enzymes can damage the lining of the G.I. tract if natural protective factors are not functioning normally. Causes of gastrointestinal diseases are use of aspirin, alcohol and tobacco, poor diet (too many fried, fatty foods, sugar and refined foods), poor food combining, drinking with meals. Various diagnostic tests that can be performed for gastrointestinal diseases are Colonoscopy, ERCP, Flexible Sigmoidoscopy, Lower GI Series, Liver Biopsy, Upper GI Series, Upper Endoscopy.